First record of Clito aberrans (Lepidoptera; Hesperiidae) in a Caatinga–Atlantic Forest ecotone, Brazil - Dantas, Caique (2025)
This study reports the first record of the butterfly species Clito aberrans (Draudt, 1924), belonging to the family Hesperiidae (Lepidoptera) in the state of Bahia, Brazil. The specimen was collected in January 2023 using an entomological net at the Campus of the Universidade Estadual de Feira de Santana (UEFS), an area located within the Caatinga-Atlantic Forest ecotone in the municipality of Feira de Santana, Bahia. Images of C. aberrans and a map illustrating the species occurrence in Bahia are also provided. This new record underscores the importance of expanding taxonomic research in the state of Bahia and the Northeast region, as well as mapping the species distribution across Brazil.